The role of radiomics in tongue cancer: A new tool for prognosis prediction. Issue 4 (13th February 2023) - Mossinelli, Chiara; Tagliabue, Marta; Ruju, Francesca; Cammarata, Giulio; Volpe, Stefania; Raimondi, Sara; Zaffaroni, Mattia; Isaksson, Johannes Lars; Garibaldi, Cristina; Cremonesi, Marta; Corso, Federica; Gaeta, Aurora; et al.
Abstract: Background: Radiomics represents an emerging field of precision‐medicine. Its application in head and neck is still at the beginning. Methods: Retrospective study about magnetic resonance imaging (MRI) based radiomics in oral tongue squamous cell carcinoma (OTSCC) surgically treated (2010–2019; 79 patients). All preoperative MRIs include different sequences (T1, T2, DWI, ADC). Tumor volume was manually segmented and exported to radiomic‐software, to perform feature extraction. Statistically significant variables were included in multivariable analysis and related to survival endpoints. Predictive models were elaborated (clinical, radiomic, clinical‐radiomic models) and compared using C‐index. Results: In almost all clinical‐radiomic models radiomic‐score maintained statistical significance. In all cases C‐index was higher in clinical‐radiomic models than in clinical ones. ADC provided the best fit to the models (C‐index 0.98, 0.86, 0.84 in loco‐regional recurrence, cause‐specific mortality, overall survival, respectively). Conclusion: MRI‐based radiomics in OTSCC represents a promising noninvasive method of precision medicine, improving prognosis prediction before surgery.